EFFECT OF ANTISTRESS AGENTS ON THE PERFORMANCE OF BROILER UNDER DIFFERENT MANAGEMENT SYSTEMS - KUMAR, SANJAY; PRASAD, C. M.; KUMARI, SUSHMA (Indian Journal of Animal Production and Management, 2017)
ABSTRACTA study was conducted to investigate the effect of different anti-stress agents on thegrowth performance and survivability of broilers. Four hundred and eight day old chicks wererandomly divided into two groups and reared under cage and deep litter system respectively.Each group was further divided into 4 sub-groups of 51 chicks each and were given differentanti-stress agents along with standard broiler ration. Group T 1 & T 5 were treated as Control,Group T 2 & T 6 were treated with Zeetress , Group T 3 & T 7 were treated with Glucose andGroup T 4 & T 8 were treated with honey under cage and deep litter system respectively. Thebody weight gain and Feed Conversion. Ratio was significantly (P